2014
DOI: 10.1136/bmj.f7493
|View full text |Cite
|
Sign up to set email alerts
|

Home energy efficiency and radon related risk of lung cancer: modelling study

Abstract: Objective To investigate the effect of reducing home ventilation as part of household energy efficiency measures on deaths from radon related lung cancer.Design Modelling study. Setting England.Intervention Home energy efficiency interventions, motivated in part by targets for reducing greenhouse gases, which entail reduction in uncontrolled ventilation in keeping with good practice guidance.Main outcome measures Modelled current and future distributions of indoor radon levels for the English housing stock and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 33 publications
(27 reference statements)
2
80
0
Order By: Relevance
“…Furthermore, the building permeabilities were decreased by 5 m 3 /h/m 2 to reflect improvements to building airtightness following retrofits. 24 The future building envelope characteristics can be seen in Table 2. In multiple-occupancy buildings, dwellings were modelled at ground, middle and top-floor heights.…”
Section: Archetype Developmentmentioning
confidence: 99%
“…Furthermore, the building permeabilities were decreased by 5 m 3 /h/m 2 to reflect improvements to building airtightness following retrofits. 24 The future building envelope characteristics can be seen in Table 2. In multiple-occupancy buildings, dwellings were modelled at ground, middle and top-floor heights.…”
Section: Archetype Developmentmentioning
confidence: 99%
“…are implemented. Research efforts including both simulations and field measurements have demonstrated increased negative health effects or poor IAQ in efficient or retrofitted residences that did not sufficiently address IAQ provisions (Emmerich et al, 2005;Milner et al, 2014;Offermann, 2009;Wilson et al, 2013). Yet, other research efforts that have consistently included IAQ best practices have demonstrated improved health outcomes and generally reduced pollutant levels (Breysse et al, 2011;Jacobs, 2013;Kovesi et al, 2009;Leech et al, 2004;Noris et al, 2013a;Weichenthal et al, 2013).…”
Section: Additional Indoor Pollutantmentioning
confidence: 99%
“…Indeed, increasing airtightness can elevate mean radon concentrations by 56.6%. 19 This effect makes radon a more pressing concern in countries with colder climates such as Canada. • Home floor-plan sizes in Alberta have steadily increased over time.…”
Section: Discussionmentioning
confidence: 99%